Applications of Linear Programming on Diet Problem for Subways’ Sets Menu in Malaysia - Khalidah Irdina Khalid; Nurul Farihan Mohamed; Abdul Rahim Khairul Anuar (Semarak Ilmu Publishing, 2024)
Indexed by Scopus